Mechanistic studies of MALAT1 in respiratory diseases - Wu, Wenzheng; Wang, Shihao; Zhang, Lu; Mao, Beibei; Wang, Bin; Wang, Xiaoxu; Zhao, Dongsheng; Zhao, Pan; Mou, Yunying; Yan, Peizheng (Frontiers in Molecular Biosciences, 2022)
Abstract: Background: The incidence and mortality rates of respiratory diseases are increasing. Recent studies demonstrated the involvement of the lncRNA MALAT1 in various respiratory diseases. In vascular endothelial and cancer cells, MALAT1 expression triggers various risk factors such as proinflammatory cytokine expression, cancer cell proliferation and metastasis, and increased endothelial cell permeability. Methods: In this review, we introduce RCI analysis from the lncRNA database to obtain differences in MALAT1 expression in different cell lines and at different locations in the same cell, and summarize the molecular mechanisms of MALAT1 in the pathophysiology of respiratory diseases and its potential therapeutic application in these conditions. Results: MALAT1 is an important regulatory role of lncRNA with a wide range of roles in respiratory diseases. We illustrate and summarize the role of MALAT1 in the regulation of related respiratory diseases based on the available studies. Simultaneous screening of relevant targets. We hope that this study will shed light on the underlying mechanisms by which MALAT1 regulates respiratory diseases and suggest that it may serve as a therapeutic target for the development of new drug treatments effective against these diseases to inform subsequent studies. Conclusion: Our results suggest that lncRNA MALAT1 is an important regulatory biomarker for respiratory disease. Targeting the regulation MALAT1 could be an important application for the future treatment of respiratory diseases.